1994
DOI: 10.1093/oxfordjournals.annonc.a058806
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2′-deoxycytidine induces growth inhibition and upregulation of epidermal growth factor receptor on human epithelial cancer cells

Abstract: We suggest a role for 5azaCdR in enhancing the efficacy of therapeutic approaches involving the use of anti-EGF-R immunoconjugated for the imaging and the treatment of human epithelial neoplasias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…We selected the relatively unresponsive MiaPaCa2 cell line, as well as the PaCa44 and CFPAC1 cell lines, which show strong inhibition of cell proliferation associated with arrest or delay in S or G2/M phases. Low rates of induction of apoptosis confirmed that 5-aza-CdR treatment produces a predominantly cytostatic effect in these pancreatic cancer cell lines, as observed for other cancer cell lines (Davidson et al, 1992;Caraglia et al, 1994;Karpf et al, 1999;Sato et al, 2003a).…”
Section: Discussionsupporting
confidence: 69%
“…We selected the relatively unresponsive MiaPaCa2 cell line, as well as the PaCa44 and CFPAC1 cell lines, which show strong inhibition of cell proliferation associated with arrest or delay in S or G2/M phases. Low rates of induction of apoptosis confirmed that 5-aza-CdR treatment produces a predominantly cytostatic effect in these pancreatic cancer cell lines, as observed for other cancer cell lines (Davidson et al, 1992;Caraglia et al, 1994;Karpf et al, 1999;Sato et al, 2003a).…”
Section: Discussionsupporting
confidence: 69%
“…The triggering of protective response to anticancer activity of biological agents is not an occasional event and several preclinical findings support the hypothesis that a reactive response can be induced in cancer cells that is translated in an overactivation of other signaling pathways [65,66].…”
Section: Reviewmentioning
confidence: 77%
“…Our results together with previously reported data on increased EGFR mRNA in a glioblastoma cell line [46] and the presence of the IFN-regulatory factor-1 in the EGFR promoter region [47] all support the hypothesis that IFNα can directly regulate EGFR expression.The supra-additive anti-proliferative effect achieved by combining gefitinib with IFNα may indicate that the process of HER1/EGFR up-regulation itself has the potential to enhance sensitivity to its inhibitors. However, an equally plausible hypothesis is that this is a secondary effect via changes in the cell growth status [48,49,50,51]. Thus, increased receptor expression could be part of a homeostatic cellular response to the strong anti-proliferative stimuli of the combined treatment.…”
Section: Discussionmentioning
confidence: 99%